Development of WEB-Based Correspondence Management Application Programs Faculty of Mathematics and Natural Sciences UNIMED - Nur Kholiza; Faiz Ahyaningsih (Kaunia: Integration and Interconnection Islam and Science Journal, 2021)
Faculty of Mathematics and Natural Sciences which is one of the faculty at Unimed in organizing the activities scheduled and archive mail incoming and outgoing mail is still using manual diary. This is less efficient because it will be difficult to find so many archives of letters that have been stored for a long time. Currently, technological advances in the world are growing rapidly and are very much needed. Especially with the emergence of the Corona Virus Disease (Covid-19) Pandemic, most of the community's activities are disrupted so that activities are carried out online. Likewise with the student activities of FMIPA Unimed. Now students carry out lectures online. However, for final year students who want to apply for a thesis research letter or active students who want to apply for a scholarship need an active college letter, they must come to campus to take care of the files in order to get the required letter. Therefore, there is a need for a correspondence management application in the administration of FMIPA Unimed so that FMIPA Unimed students can take care of the required letters online, employees can speed up searching for mail data and print out their letter reports. This application is designed web-based using PHP and MySQL. This application has the ability to be accessed anywhere by admins, employees and students so that employees can manage mail with a user login, be it adding, updating, deleting, uploading, downloading and searching for letters and printing mail reports. In addition, it also makes it easier for students to take care of research letters and active lecture letters online until the letters are completed and can be downloaded. This application also provides a place to send messages to each other between employees and students.